The dark side of fashion: An empirical analysis of contemporary slave labor in the fashion industry - Veloso , Carla Sendon Ameijeiras (Seven Editora, 2024)
Despite the abolition of slavery, slave labor still exists. In a new socio-historical context, the chains and slave quarters have been left behind, and today the workers are lured, subjected to degrading conditions and have their fundamental rights curtailed. Contemporary slave labor has emerged as a research theme in Organizational Studies since the early 2000s, drawing attention to the use of this practice. In Brazil, it is a matter of great concern, justifying itself, after denunciation in the Inter-American Court of Human Rights and confession of the use of this practice in the XXI century. Contemporary slave labor is found in the most diverse economic activities, from charcoal to textile industries or even trades, whether in urban or rural areas. In this article we will analyze the view of some consumers about consumption in companies that were denounced using slave labor. We adopt the fashion industry as the focus of research because it obscures the reflection of consumers who, when shopping, feel like entering another world: beauty and fantasy, in search of their own satisfaction. Added to this is the fact that the Brazilian fashion industry is one of the largest in the world (ABIT, 2015). This article will use quantitative and qualitative methodology, as well as existing legal literature. DOI:https://doi.org/10.56238/sevened2023.006-098